2006
DOI: 10.1074/jbc.m606059200
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Processing of OPA1 Links Mitochondrial Dysfunction to Alterations in Mitochondrial Morphology

Abstract: Many muscular and neurological disorders are associated with mitochondrial dysfunction and are often accompanied by changes in mitochondrial morphology. Mutations in the gene encoding OPA1, a protein required for fusion of mitochondria, are associated with hereditary autosomal dominant optic atrophy type I. Here we show that mitochondrial fragmentation correlates with processing of large isoforms of OPA1 in cybrid cells from a patient with myoclonus epilepsy and ragged-red fibers syndrome and in mouse embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
313
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 385 publications
(339 citation statements)
references
References 48 publications
24
313
1
1
Order By: Relevance
“…12 The activity of OPA1 is regulated by proteolytic cleavage. Paraplegin, YME1L and OMA1 proteases have all been shown to cleave OPA1, [13][14][15][16][17] thus implicating them in the regulation of mitophagy. The mitochondrial rhomboid protease presenilin-associated rhomboid-like (PARL) is also implicated in regulating mitophagy by cleaving PINK1, 18,19 a kinase required for mitophagy.…”
mentioning
confidence: 99%
“…12 The activity of OPA1 is regulated by proteolytic cleavage. Paraplegin, YME1L and OMA1 proteases have all been shown to cleave OPA1, [13][14][15][16][17] thus implicating them in the regulation of mitophagy. The mitochondrial rhomboid protease presenilin-associated rhomboid-like (PARL) is also implicated in regulating mitophagy by cleaving PINK1, 18,19 a kinase required for mitophagy.…”
mentioning
confidence: 99%
“…For example, it has been reported that Paraplegin, an IMM mAAA metalloprotease, participates in the cleavage of Opa1 to produce a short isoform that is fusion incompetent. 79,80 It should be noted that Paraplegin faces the matrix and that the mitochondrial processing peptidase already trims most of the matrix residues of Opa1. 81 At this stage a plausible scenario deserving further investigation is that Paraplegin and Parl somehow cooperate in the cleavage of Opa1.…”
Section: Parl: a Shortcut To Regulate Apoptosismentioning
confidence: 99%
“…Aging hypothesis: Deceleration of fusionfission cycles improves mitochondrial quality control Microscopic investigations revealed that mitochondria are organized within a highly dynamic network that is governed by mitochondria undergoing cycles of fusion and fission that result in the mixing of their molecular content [28][29][30][31][32]. Mitochondrial dynamics and consequently changes in mitochondrial morphology are regulated at multiple levels including limited proteolysis, ubiquitinylation, phosphorylation, sumoylation, and disulfide formation of critical fusion and/or fission factors [20,[33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…In this context it is important to note that it was shown in yeast as well as in mammalian cells that the bioenergetic state of mitochondria is linked to the mitochondrial morphology [41,42,45,46]. When mitochondrial function is impaired, the fusion machinery is inactivated, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation